Concomitantly discovered visceral artery aneurysms do rarely grow during cancer therapy. Issue 3 (2nd December 2021) - von Rose, Aaron Becker; Kobus, Kathrin; Bohmann, Bianca; Trenner, Matthias; Wahida, Adam; Eckstein, Hans‐Henning; Bassermann, Florian; von Heckel, Korbinian; Wolk, Steffen; Reeps, Christian; Schwaiger, Benedikt J.; Eilenberg, Wolf‐Hans; et al.
Abstract: Visceral artery aneurysms (VAA) are a rare entity of arterial aneurysms with the imminent threat of rupture. The impact of cancer and chemotherapy on the growth of VAAs is unknown. A retrospective dual center cohort study of patients with concomitant VAA and different types of cancer was conducted and the impact of various chemotherapeutic agents on VAA growth was studied by sequential CT analysis. For comparison, a non‐cancer all comer cohort with VAAs and no cancer was studied to compare different growth rates. The primary endpoint was aneurysm progress or regression >1.75 mm. Chi‐square test, Fisher's exact test and Mann–Whitney test was used for statistical comparison. In the 17‐year‐period from January 2003 to March 2020, 59 patients with 30 splenic artery aneurysms, 14 celiac trunk aneurysms, 11 renal artery aneurysms and 4 other VAA and additional malignancy were identified. 20% of patients suffered from prostate cancer, the rest were heterogeneous. The most prevalent chemotherapies were alkylating agents (23%), antimetabolites (14%) and mitose inhibitors (10%). Eight patients had relevant growth of their VAA and one patient showed diameter regression (average growth rate 0.1 ± 0.5 mm/year). Twenty‐nine patients with 14 splenic, 11 RAAs (seven right) and 4 celiac trunk aneurysms were available in the non‐cancer comparison cohort (average growth rate 0.5 ± 0.9 mm/year, p = 0.058). However, the growth rate of patients receiving operative treatment for relevant VAA growth was significantly higher ( p = 0.004). VAAs grow rarely, and rather slow. Cancer and/or chemotherapy do not significantly influence the annual growth rate. Additional control examinations seem unnecessary.